Patterns, Causes, and Consequences of Anthropocene Defaunation - Young, Hillary S.; McCauley, Douglas J.; Galetti, Mauro [UNESP]; Dirzo, Rodolfo (Annual Reviews, 2016)
Anthropocene defaunation, the global extinction of faunal species and populations and the decline in abundance of individuals within populations, has been predominantly documented in terrestrial ecosystems, but indicators suggest defaunation has been more severe in freshwater ecosystems. Marine defaunation is in a more incipient stage, yet pronounced effects are already apparent and its rapid acceleration seems likely. Defaunation now impacts the planet's wildlife with profound cascading consequences, ranging from local to global coextinctions of interacting species to the loss of ecological services critical for humanity. Slowing defaunation will require aggressively reducing animal overexploitation and habitat destruction; mitigating climate disruption; and stabilizing the impacts of human population growth and uneven resource consumption. Given its omnipresence, defaunation should receive status of major global environmental change and should be addressed with the same urgency as deforestation, pollution, and climatic change. Global action is needed to prevent defaunation's current trajectory from catalyzing the planet's sixth major extinction.
Keywords: Animal conservation; Animal overexploitation; Defaunation cascades; Freshwater fauna; Marine fauna; Terrestrial fauna